PELATIHAN MANAJEMEN TATA KELOLA DANA SEDEKAH MELALUI KEGIATAN NASI JUMAT BAROKAH DAN SANTUNAN HARI RAYA (Pengabdian Masyarakat bersama Komunitas Sobat Shalihah Sidoarjo) - Muhammad Yusuf Aria Widjaja; Farhadi Arfiansyah; Muhlis Muhlis; Andro Agil Nur Rakhmad; Nurul Istiqomah (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
Community empowerment makes efforts to increase the independence of individuals and groups of the public in providing improvement and development of self-quality for the better. The existence of community groups in contributing to the distribution of welfare distribution has an appeal to the social programs being run. The concept of sadaqa  is considered to be an intermediary for people who have more funds and distributed to people who need resgistered to the asnaf group contained in the al-Qur'an. The Sobat Salihah Community with sadaqa of Nasi Jumber program seeks to improve competence in the management of sadaqa fund management. The training is carried out by extension methods through several stages, including, 1) Planning for program activities; 2) Implementation of activity plans 3) Implementation of evaluation and reporting. This training seeks an effort to increase awareness and concern for donors to communities affected by the Covid-19 pandemic. This activity involved community administrators, 205 donors who had raised funds and 345 beneficiaries for distribution to predetermined programs.